An Appraisal of the Al Mahdi Order on Reparations and Its Innovative Elements: Redress for Victims of Crimes against Cultural Heritage. (27th June 2018) - Capone, Francesca
Abstract: On 17 August 2017, the International Criminal Court (ICC) handed down its order on reparations in the Al Mahdi case. This milestone marks the first time the ICC has awarded reparations to victims of crimes against cultural heritage. According to Trial Chamber VIII, which issued the order, the reparation framework provided by the Court's limited jurisprudence is also capable of addressing the consequences stemming from crimes against cultural heritage. This framework is currently composed of principles on reparation and lays down those key elements which must be contained in the order, as identified in the Lubanga case and reasserted in the order on reparations issued in the Katanga case. Nonetheless, the reparations awarded in the Al Mahdi case present an innovative character, which emerges quite strongly in relation to some aspects. The innovative elements are as follows: identification of relevant victims; prioritization of reparations for individuals; and the challenges in implementing guarantees of non-repetition. After offering a brief overview of the case under analysis, this article focuses on the main features of the Al Mahdi order on reparations, which, in this author's view, underline the ICC's propensity to enhance its role in the discourse around reparation, by undertaking considerable efforts to provide victims of the crimes under its jurisdiction with adequate, effective and prompt remedial measures.